Filsafat, Teologi dan Pemajuan Kebudayaan - Paul Richard Renwarin (Sekolah Tinggi Filsafat Seminari Pineleng, 2020)
This article deals with the kern question, “what can the philosophy and theology contribute to develop the culture, as the Indonesian law number 15 on the year of 2017 challenges?” Answering this question, I look for the conception of culture, the core elaboration of philosophy and theology, and their methods of research. The meeting point of the trio is the human experience; both philosophy and theology concern of the inner and deeper side of human experience, i.e. beliefs, values, and fundamental assumptions of life.